Genetics of Asthma. (25th December 2015) - Hizawa, Nobuyuki
Abstract : Asthma runs strongly in families and has a heritability rate of up to 60%. Genetic studies offer a structured means for understanding the causes of asthma and for identifying targets of treatment for the syndrome. As with studies of other common complex diseases, genetic studies of asthma have led to considerable advances in the understanding of this disease. Genome‐wide association studies have greatly advanced the identification of the most important genes predisposing individuals to airway diseases. Several genes act in pathways that communicate the presence of epithelial damage to the adaptive immune system ; identification of these genes has provided a new focus for the development of effective therapies. Genetic findings have also led to a reassessment of the primacy of atopy in asthma and eczema (atopic dermatitis) ; these findings indicate that atopy is secondary to epithelial damage or other events in both diseases. Despite these advances, only a small component of the overall genetic contribution to asthma has been identified. This missing heritability may be due to multiple genes of small effects (polygenes), rare highly penetrant mutations, or epigenetic modifications of gene function. Further work is necessary to understand the biological consequences of the known susceptibility variants ; the most immediate challenge in this field is the systematic analysis of the precise functions of these genes in the pathogenesis of asthma. Detailed functional dissection of the roles of these genes in asthma will point the way to new therapies for the disease.